Refocusing Faculty Development: The View from an Adult Learning Perspective - Patricia A. Lawler; Kathleen P. King (Adult Education Research Conference, 2000)
The Adult Learning Model of Faculty Development draws from the research, theory and practice of adult learning and adult education program planning. This new model recognizes faculty as adult learners and faculty development as adult education. It offers strategies for effective initiatives.